THE INFLUENCE OF PERCEIVED ORGANIZATIONAL SUPPORT AND JOB CHARACTERISTICS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Nadifa, Tasya (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of perceived organizational support and job characteristics on organizational citizenship behavior in nurses at Unipdu Medika Jombang Hospital. This research uses descriptive analysis method which is carried out through data collection in the field. The population and sample were nurses at the Unipdu Medika Hospital Jombang, amounting to 32 nurses, data analysis using multiple linear regression statistical methods and hypothesis testing with t test and coefficient of determination using SPSS 21. Based on the results of the study showed that perceived organizational support and characteristics work has an impact and is relevant to organizational citizenship behavior in nurses at Unipdu Medika Jombang Hospital